Method of manufacturing fibers
By using ionic liquid as a combination of solvent and carbon nanomaterials, the problems of high solvent costs and difficult thermal behavior control in the production of lignin fibers in the prior art are solved, and high carbon yields and improved graphite structure are achieved, and production costs are reduced.
Patent Information
- Application Number
- CN202380053611.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-31
- Filing Date
- 2023-05-31
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art is difficult to use non-toxic, low-cost solvents when producing lignin fibers, and it is difficult to control the thermal behavior of lignin to obtain appropriate melting behavior and oxidative stability.
A method of making fibers is provided by providing a spinning stock solution containing an ionic liquid as a solvent, lignin dissolved in the solvent, and carbon nanomaterial dispersed in the solvent, and extruded into a solidification bath to obtain the fibers.
This method can use non-toxic and low-cost solvents, which improves the carbon yield of lignin fibers and improves the graphite structure and reduces production costs.
Smart Images

Figure BDA0005240409960000041 
Figure BDA0005240409960000081 
Figure BDA0005240409960000091
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing fibers, the method comprising: providing a spinning solution, the spinning solution comprising a solution solvent, lignin dissolved in the solution solvent, and carbon nanomaterials dispersed in the solution solvent, wherein the solution solvent comprises an ionic liquid and optionally further comprises water; and extruding the spinning solution into a coagulation bath to obtain one or more fibers. Background Art
[0002] Carbon fiber (CF) is a strength material that can be used to produce carbon fiber reinforced composite materials, which are desirable lightweight building materials. Carbon fiber is produced by pyrolysis of a precursor fiber made of polyacrylonitrile (PAN) and mesophase petroleum pitch. However, these two main precursors are derived from petroleum and are therefore non-renewable. For PAN, the use of toxic spinning solvents (such as DMF) and the generation of toxic byproducts (such as HCN) during carbonization have caused additional environmental and health issues. The high cost associated with precursor manufacturing and energy-intensive high-temperature processing also limits the use of carbon fiber composites to the high-end market, and becomes an obstacle to the rapid growth of the market.
[0003] Lignin has the potential to become a more low-cost and renewable alternative precursor, because lignin is an easily available biopolymer with high carbon content. Lignin is attractive because of its sustainable source, low cost and relatively high fiber yield after carbonization. During paper and pulp manufacturing, more than 7,000 tons of lignin will be extracted every year. Commercial lignin-based carbon fiber can provide additional income for wood processing biorefinery, which currently burns most of lignin to produce heat and electricity instead of value-added products, thereby supporting the economy of the developing renewable chemical industry.
[0004] Most research involving the production of lignin fibers has focused on melt spinning at about 200°C, typically using copolymers. Although the process is attractive because it avoids solvents, it is difficult to control the thermal behavior of lignin to obtain suitable melt behavior, and oxidative stabilization is slow and fiber shape is difficult to maintain.
[0005] Wet (coagulation) spinning of pure unmodified lignin has not been demonstrated, probably due to its low average molar weight. Wet spinning can be achieved by blending lignin with another fiber-forming polymer such as cellulose. Solvents reported to date for wet spinning include DMSO ( M. et al., Wet-Spinning and Carbonization of Lignin-Polyvinyl Alcohol Precursor Fibers. Advanced Sustainable Systems, 2019; Lu, C. et al., ACS Sustainable Chemistry and Engineering, 2017, 5(4), 2949–2959).
[0006] In addition, the ionic liquid (IL) 1-ethyl-3-methylimidazolium acetate [EMim][OAc] has been used to form precursor lignin / cellulose fibers with pure water as a coagulant (Bengtsson, A. et al., Wood Research (Holzforschung) 2018, 72(12), 1007–1016; Vincent, S. et al., ACS Sustainable Chemistry and Engineering 2018, 6(5), 5903–5910). The ionic liquid 1,5-diazabicyclo[4.3.0]non-5-ene acetate [DBNH][OAc] has also been used to produce carbon fibers derived from 50 / 50% kraft lignin / cellulose precursor fibers (Ma, Y. et al., ChemSusChem 2015, 8(23), 4030–4039). However, these methods require expensive ionic liquids that must be strictly dried to dissolve cellulose, which is a challenge for commercialization.
[0007] Therefore, there is a need for new methods for producing lignin fibers that enable the use of non-toxic, low-cost solvents. It is also desirable to produce lignin fibers with improved graphitic structure and higher carbon yields. Summary of the invention
[0008] In a first aspect, the present invention provides a method for manufacturing fibers, the method comprising: providing a spinning solution, the spinning solution comprising a solution solvent, lignin dissolved in the solution solvent, and a carbon nanomaterial, wherein the solution solvent comprises an ionic liquid and optionally water; and extruding the spinning solution into a coagulation bath to obtain one or more fibers.
[0009] In a second aspect, there is provided a fiber obtainable by the method of the first aspect.
[0010] In a third aspect, the present invention provides a spinning solution, the spinning solution comprising a solution solvent, lignin and a carbon nanomaterial, wherein the solution solvent comprises an ionic liquid and optionally water. The spinning solution can be as described in relation to the first aspect.
[0011] In a fourth aspect, provided herein is a dispersion comprising carbon nanotubes and [DMBA][HSO4]. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Embodiments of the present disclosure will now be described, by way of example only, and with reference to the accompanying drawings, in which:
[0013] Figure 1 Shown is a shear rate sweep of fibers produced as described herein.
[0014] Figure 2 Shown is a strain sweep of a fiber produced as described herein.
[0015] Figure 3 Shown is a frequency sweep of a fiber produced as described herein.
[0016] Figure 4 Shown is a thermogravimetric analysis (TGA) graph of a TGA experiment performed in air (LNCF = Lignin Nanocomposite Fiber).
[0017] Figure 5 The TGA curve for heating carried out in nitrogen is shown.
[0018] Figure 6 Shear rate scans of the 0 day stock solution and the 30 day stock solution are shown. DETAILED DESCRIPTION
[0019] In a first aspect, the present invention provides a method for manufacturing fibers, the method comprising: providing a spinning solution, the spinning solution comprising a solution solvent, lignin dissolved in the solution solvent, and a carbon nanomaterial, wherein the solution solvent comprises an ionic liquid and optionally water; and extruding the spinning solution into a coagulation bath to obtain one or more fibers.
[0020] The fiber produced by this method can be called lignin fiber. The fiber contains lignin and carbon nanomaterial. The fiber can be used as a precursor fiber for producing carbon fiber or as a raw material for other fiber-based materials.
[0021] The stock solution solvent is a solvent in which lignin can be dissolved. Preferably, the stock solution solvent is a solvent in which the solubility of cellulose is lower than the solubility of lignin. More preferably, the stock solution solvent does not dissolve cellulose.
[0022] The spinning solution preferably comprises a cellulose loading of no more than 10% relative to the mass of the spinning solution, excluding the mass of cellulose, lignin and carbon nanomaterial (i.e., w / w%). Preferably, the cellulose loading is no more than 5%, no more than 2% or no more than 1%. The spinning solution is preferably substantially free of cellulose. Undissolved cellulose can be removed, for example, by filtration.
[0023] The water content of the stock solution solvent can be 0-30wt%, 0-20wt%, 0-15wt%, 0-10wt% or 0-5wt%. The water content of the stock solution solvent can be at least 1wt%, at least 2wt% or at least 3wt%. The water content of the stock solution solvent is calculated based on the mass of water present relative to the total mass (i.e., w / w%) of the stock solution solvent. The stock solution solvent can further include ethanol. The stock solution solvent can include 0-20wt% ethanol calculated relative to the total mass (i.e., w / w%) of the stock solution solvent, such as 1-20wt% ethanol, preferably 5-15wt% ethanol.
[0024] When the stock solution solvent comprises ethanol, the mass ratio of ionic liquid:ethanol may be 3:1 to 15:1, preferably 5:1 to 12:1.
[0025] Lignin may be present in the spinning solution in a loading amount of at least 5wt%, preferably at least 10wt%, relative to the mass of the spinning solution, excluding the mass of lignin and carbon nanomaterials. Lignin may preferably be present in a loading amount of 10-50wt%, 10-40wt%, 10-30wt%, relative to the mass of the spinning solution, excluding the mass of lignin and carbon nanomaterials. The lignin may be, for example, hardwood lignin, softwood lignin, grass lignin or other lignin (e.g., genetically modified lignin). The lignin may be hardwood lignin. The lignin may be ionoSolv lignin or kraft lignin, such as LignoBoost lignin.
[0026] The carbon nanomaterial may be present in the spinning solution in a loading amount of at least 0.001wt%, at least 0.01wt%, or at least 0.1wt% relative to the mass of the spinning solution, excluding the mass of lignin and the carbon nanomaterial. The carbon nanomaterial may be present in a loading amount of 0.001-10wt%, 0.001-8wt%, 0.01-8wt%, 0.1-5wt%, 0.1-1wt%, or 0.3-0.7wt% relative to the mass of the spinning solution, excluding the mass of lignin and the carbon nanomaterial. The carbon nanomaterial may be present in a loading amount of about 0.5% relative to the mass of the spinning solution, excluding the mass of lignin and the carbon nanomaterial.
[0027] The weight ratio of lignin to carbon nanomaterial in the spinning solution may be 5:1 to 10000:1, preferably 5:1 to 5000:1, more preferably 10:1 to 1000:1, and even more preferably 20:1 to 200:1.
[0028] The water content of the spinning solution can be 0-30wt%, 0-20wt%, 0-15wt%, 0-10wt% or 0-5wt%. The water content of the stock solution solvent can be at least 1wt%, at least 2wt% or at least 3wt% calculated based on the mass of water present relative to the mass of the spinning solution, excluding the mass of lignin and carbon nanomaterials.
[0029] The carbon nanomaterial may include carbon nanotubes, carbon nanoribbons, graphene nanoplates or a combination thereof. Preferably, the carbon nanomaterial includes carbon nanotubes. Preferably, the carbon nanotubes are single-walled carbon nanotubes (SWCNTs).
[0030] The carbon nanomaterial may be dispersed in the stock solution solvent.
[0031] The ionic liquid may be any ionic liquid as described herein. Preferably, the ionic liquid comprises a cation and an anion selected from the group consisting of: C 1-20 Alkyl sulfate ion ([alkyl SO4] - ), C 1-20 Alkylsulfonate ion ([alkylSO3] - ), bisulfate ion ([HSO4] - ), bisulfite ion ([HSO3] - ), dihydrogen phosphate ion ([H2PO4] - ), hydrogen phosphate ion ([HPO4] 2- ), chloride ion (Cl - ), bromide ion (Br - ), trifluoromethanesulfonate ion ([OTf] - ), formate ion ([HCOO] - ) and acetate ions ([MeCO2] - ). Preferably, the anion is selected from [HSO4] - and [HCOO] - .
[0032] The cation may be an aprotic cation or a protic cation, preferably a protic cation. The cation may contain a nitrogen-containing heterocyclic moiety or may be a cation of formula I.
[0033]
[0034] Among them A1 To A 4 Each independently selected from H, aliphatic, C 3-6 Carbon ring, C 6-10 Aryl, alkaryl and heteroaryl.
[0035] The ionic liquid may be an [alkylammonium][HSO4] or [alkylammonium][HCOO] ionic liquid.
[0036] The ionic liquid can be N,N-dimethylbutylammonium hydrogen sulfate ([DMBA][HSO4]), 1-butylimidazolium hydrogen sulfate ([HBim][HSO4]), triethylammonium hydrogen sulfate ([TEA][HSO4]), N-methylbutylammonium hydrogen sulfate ([MBA][HSO4]), 1-methylimidazolium formate ([HMim][HCOO]), N,N-dimethylbutylammonium formate ([DMBA][HCOO]) or a mixture thereof. Preferably, the ionic liquid is [DMBA][HSO4].
[0037] The ionic liquid may be [DMBA][HSO4]. [DMBA][HSO4] exhibits exceptional ability in fractional extraction of lignin from lignocellulosic biomass, while having a lower melting point (and therefore viscosity) than other ionic liquids containing bisulfate anions, and an estimated production cost of about $1 / kg (similar to [TEA][HSO4]), making it cheaper than most ionic liquids and also DMSO. In addition, the ammonium bisulfate ionic liquid may be recyclable.
[0038] In the method described herein, wet (coagulation) spinning is used to form fibers. This involves extruding a spinning solution into a coagulant to form fibers. The coagulant may be contained in a coagulation bath. The coagulant may contain water, preferably deionized (DI) water. The coagulant may consist essentially of water. As an alternative, the coagulant may contain water and an ionic liquid. The ionic liquid may be any ionic liquid as described herein, and preferably, the same as the ionic liquid present in the stock solution solvent. The ionic liquid may be present in the coagulant at no more than 60wt%, no more than 30wt%, or no more than 15wt%, preferably 1-60wt%, 1-30wt% or 1-15wt%, more preferably 5-10wt% (based on the total mass of the coagulant). In another alternative, the coagulant comprises water and sodium sulfate (Na2SO4). For example, the coagulation bath may contain an aqueous sodium sulfate solution having a concentration of 0.5-1.5M, preferably about 1M.
[0039] The fibers may be extruded using any suitable wet spinning process, for example using a continuous spinning line. The fibers may be extruded into a rotating bath.
[0040] The spinning solution can be prepared by a method comprising:
[0041] a) dissolving lignin in a stock solvent to obtain a lignin solution;
[0042] b) combining the lignin solution with a carbon nanomaterial; and
[0043] c) dispersing the carbon nanomaterial in the stock solution solvent to obtain a spinning stock solution.
[0044] Dispersion can be performed by shearing. Shearing can be performed to obtain a dispersion of the carbon nanomaterial, for example using a pestle and mortar, a shear mixer such as a Banbury mixer, a two-roll mill, a three-roll mill, a centrifugal mixer, a bead mill, a Silverson mixer or a jet mill.
[0045] The dissolution of the lignin may be performed at a temperature of 10°C to 200°C, preferably 10°C to 100°C, more preferably 20°C to 100°C, 20°C to 60°C or 20°C to 30°C.
[0046] The spinning solution can be prepared by a method comprising preparing a lignin solution and combining the lignin solution with a carbon nanomaterial. The lignin solution can be aged before being combined with the carbon nanomaterial. As mentioned herein, the "aging" of the lignin solution refers to the period of time after the lignin solution has been prepared and before being combined with the carbon nanomaterial. During aging, the lignin solution can be kept at room temperature or can be heated, for example, at a temperature of at least 30°C, at least 60°C, such as up to 150°C. Aging can occur for at least 2 minutes, at least 5 minutes, at least 30 minutes, at least 1 hour, at least 1 day, at least 5 days or at least 10 days. The lignin solution can be prepared by: (a) contacting a lignocellulosic biomass comprising lignin and cellulose with a composition comprising an ionic liquid and optionally water to dissolve the lignin and produce a cellulose pulp; (b) separating the cellulose pulp to obtain a mother liquor comprising the ionic liquid, water and lignin; and (c) optionally adjusting the amount of ionic liquid and / or water in the mother liquor to obtain the lignin solution. The ionic liquid is the same ionic liquid as the ionic liquid present in the stock solution solvent. The mother liquor produced in step b) can be concentrated before step c). Preparing the spinning solution can include shearing after combining the lignin solution with the carbon nano material to obtain the spinning solution. Shearing can be performed to obtain a dispersion of the carbon nano material, for example using a pestle and mortar, a shear mixer, such as a Banbury mixer, a double roll mill, a triple roll mill, a centrifugal mixer, a bead mill, a Silverson mixer or a jet mill.
[0047] The composition comprising the ionic liquid and water mentioned in step (a) (also referred to as ionic liquid / water composition) can contain a water content of 2-40wt%, such as a water content of 5-40wt%, preferably a water content of 5-10wt%. The water content mentioned in step (a) is calculated based on the mass of water present relative to the total mass of the ionic liquid / water composition. The ionic liquid / water composition can be essentially composed of ionic liquid and water. The biomass loading in step (a) can be, for example, 10%-50% or 20%-50%, such as 30%-40% relative to the mass of the ionic liquid / water composition. Steps (a)-(c) make it possible to extract lignin, form spinning solution and form fibers without the need for a separate step of separating and / or drying lignin. This can be referred to as an integrated spinning process. The method has the potential to reduce the cost of precursor fiber production by avoiding lignin precipitation, drying and redissolution steps.
[0048] The lignocellulosic biomass contacted with the composition in step a) may be heated to a temperature of at least 70° C., preferably 100-180° C., more preferably 120-170° C. For example, the lignocellulosic biomass contacted with the composition may be heated to 120-150° C. Heating may be performed for 1 minute to 22 hours, 10 minutes to 20 hours, 10 minutes to 10 hours, 15 minutes to 8 hours, or 30 minutes to 8 hours.
[0049] The biomass can be contacted with the composition and subjected to mechanical treatment, such as stirring or vortexing, to help the dissolution of lignin and the production of cellulose pulp. Mechanical treatment can be carried out before heating. Before separating the cellulose pulp, ethanol can be added to the mixture obtained from step a). The separation of the cellulose pulp can be carried out using filtration, such as vacuum filtration. The biomass can be subjected to mechanical treatment before contacting with the composition.
[0050] The integrated spinning process allows lignin from the lignocellulosic biomass to dissolve in the stock solvent, but avoids dissolution of cellulose. Other components of the lignocellulosic biomass, such as hemicellulose, may dissolve.
[0051] The spinning dope may contain additional solutes, wherein the additional solutes may be lignocellulosic biomass components (such as hemicellulose) or hemicellulose degradation products (such as furfural).
[0052] The method may further comprise drying the one or more fibers under mechanical tension.
[0053] The method may further comprise heating the one or more fibers in air at 150-300° C. This step may be performed to thermally stabilize the one or more fibers.
[0054] The method may further comprise carbonizing the one or more fibers to obtain carbon fibers. The carbonization may comprise heating the one or more fibers to 800-3000° C., preferably 1200-1800° C., under an inert atmosphere. For example, the carbonization may be performed under nitrogen or argon, preferably nitrogen. The carbonization may be performed under tension of the fibers.
[0055] The viscosity of the spinning solution at zero shear (when measured at the spinning temperature) may be 0.3-300,000 Pa·s, such as 0.3-100,000 Pa·s or 0.3-2500 Pa·s. The zero shear rate viscosity can be measured using an AR 2000ex rheometer with a cone-plate feature (2° cone angle, 20 mm plate diameter and 53 μm gap) at 3.00×10 -6 Up to 30s -1 The spinning temperature as mentioned herein may refer to 25°C.
[0056] In a second aspect, there is provided a fiber obtainable by the method of the first aspect.
[0057] In a third aspect, the present invention provides a spinning solution, the spinning solution comprising a solution solvent, lignin and a carbon nanomaterial, wherein the solution solvent comprises an ionic liquid and optionally water. The spinning solution can be as described in relation to the first aspect.
[0058] In a fourth aspect, the present invention provides a dispersion comprising carbon nanotubes and [DMBA][HSO4]. The dispersion may be a dispersion of carbon nanotubes in any stock solvent as described herein, wherein the ionic liquid is [DMBA][HSO4]. Therefore, the stock solvent may comprise water and optionally any concentration of ethanol as described herein. The carbon nanotubes may be present in a loading of at least 0.001wt%, at least 0.01wt%, or at least 0.1wt%. The carbon nanotubes may be present in a loading of 0.001-10wt%, 0.001-8wt%, 0.01-8wt%, 0.1-5wt%, 0.1-1wt%, or 0.3-0.7wt%. The carbon nanomaterial may be present in a loading of about 0.5wt%. The carbon nanotubes may be single-walled carbon nanotubes.
[0059] Ionic Liquids
[0060] The ionic liquid referred to herein may be, for example, an ionic liquid as described in WO 2012080702, WO 2014140643 or WO2017085516, which are incorporated herein by reference.
[0061] As used herein, "ionic liquid" refers to an ionized substance (i.e., a cation and an anion). Ionic liquids typically have a melting point below about 100° C. Any of the anions listed below can be used in combination with any of the cations listed below to produce an ionic liquid for use in the present invention.
[0062] The ionic liquid may contain one of the listed anions or a mixture thereof.
[0063] The anion may be selected from C 1-20 Alkyl sulfate ion ([alkyl SO4] - ), C 1-20 Alkylsulfonate ion ([alkylSO3] - ), bisulfate ion ([HSO4] - ), bisulfite ion ([HSO3] - ), dihydrogen phosphate ion ([H2PO4] - ), hydrogen phosphate ion ([HPO4] 2- ), chloride ion (Cl - ), bromide ion (Br - ), trifluoromethanesulfonate ion ([Otf] - ), formate ion ([HCOO] - ) and acetate ions ([MeCO2] - ). For example, the anion may be selected from [MeSO4] - , [HSO4] - , [MeSO3] - , Cl - , [HCOO] - and [MeCO2] - , such as selected from chloride ion Cl - and hydrogen sulfate ion [HSO4] - or selected from [MeSO4] - , [HSO4] - , [MeSO3] - and [MeCO2] - Preferably, the anion is selected from [HSO4] - and [HCOO] - The ionic liquid may contain one of the listed anions or a mixture thereof. The ionic liquid may contain any of the cations identified herein or a mixture thereof.
[0064] The cation is preferably a protic cation, i.e. a cation capable of donating a proton (H + ).
[0065] The cations may be ammonium or phosphonium derivatives. These cations have the general formula
[0066]
[0067] in
[0068] X is N or P; and
[0069] A 1 To A 4 Each independently selected from H, aliphatic, C 3-6 Carbon ring, C 6-10 Aryl, alkaryl and heteroaryl. The aliphatic may be optionally substituted with one or more -OH.
[0070] In one embodiment, the cation is an ammonium ion, a derivative thereof, or a mixture thereof. The cation may have the formula
[0071]
[0072] in
[0073] A 1 To A 4 Each independently selected from H, aliphatic, C 3-6 Carbon ring, C 6-10 Aryl, alkaryl and heteroaryl, wherein the aliphatic group may be optionally substituted with one or more -OH groups. Preferably, A 1 To A 4 At least one of is H. Preferably, A 1 To A 4 Each is independently selected from H and aliphatic. 1 To A 4 One of them is H, and the remaining three are each independently aliphatic. 1 To A 4 Two of them are each H, and the remaining two are each independently aliphatic. 1 To A 4 One of them is aliphatic, and the remaining three are all H. Preferably, the cation is not ammonium (NH4 + ), that is, A 1 To A 4 At least one of is not H. The aliphatic may be an alkyl group, optionally substituted with one or more -OH groups, preferably C 1-6In some embodiments, the aliphatic is unsubstituted.
[0074] In one embodiment, the cation is an alkylammonium or mixture thereof (ie, a cation of the above formula, wherein A 1 To A 4 Each is independently selected from H or alkyl, wherein A 1 To A 4 At least one of the alkyl groups is not H). Preferably, this is a proton alkylammonium, although non-proton alkylammonium may also be used. Optionally, one or more of the alkyl groups may be substituted with –OH to form an alkanolammonium, which may also be referred to as an alkanolammonium. For example, the cation may be choline. As used herein, “alkylammonium” includes trialkylammonium, dialkylammonium, monoalkylammonium and alkanolammonium, including trialkanolammonium, dialkanolammonium and monoalkanolammonium. Trialkylammonium includes trimethylammonium, triethylammonium and triethanolammonium. Examples of dialkylammonium include diethylammonium, diisopropylammonium and diethanolammonium. Monoalkylammonium includes methylammonium, ethylammonium and monoethanolammonium. The ionic liquid may preferably be an [alkylammonium][HSO4] or [alkylammonium][HCOO] ionic liquid.
[0075] In one embodiment, the alkylammonium cation is selected from triethylammonium, diethylammonium, dimethylethylammonium, diethylmethylammonium, dimethylbutylammonium, diethanolammonium and choline. The alkylammonium cation can be selected from triethylammonium, diethylammonium, dimethylethylammonium, diethylmethylammonium and dimethylbutylammonium, diethanolammonium. In another embodiment, the alkylammonium cation is selected from dimethylbutylammonium, triethylammonium and methylbutylammonium.
[0076] The cation may also contain a nitrogen-containing heterocyclic moiety, as used herein, the nitrogen-containing heterocyclic moiety refers to a monocyclic or bicyclic ring system including a nitrogen atom and optionally one or more additional heteroatoms selected from N, S and O. The ring system contains 5-9 members, preferably 5 or 6 members for monocyclic groups and 9 or 10 members for bicyclic groups. The ring may be aromatic, partially saturated or saturated, and thus includes both "heteroalicyclic" groups (meaning non-aromatic heterocycles) and "heteroaryl" groups (meaning aromatic heterocycles). The cation may be selected from
[0077]
[0078] Where R 1 and R 2 Independently C 1-6 Alkyl or C 1-6 Alkoxyalkyl, and R 3 , R 4 , R 5 , R 6 , R 7 , R8 and R 9 , when present, are independently H, C 1-6 Alkyl, C 1-6 Alkoxyalkyl or C 2-6 Preferably, R 1 and R 2 It is C 1-4 alkyl, one of which is methyl, and R 3 -R 9 (R 3 , R 4 , R 5 , R 6 , R 7 , R 8 and R 9 ), when present, is H. In one embodiment, the cationic ring is an imidazolium ion or a pyridinium ion.
[0079] In one embodiment, the cation may be an imidazolium-based cation or a mixture thereof, in particular a proton-based imidazolium-based cation. In one embodiment, the imidazolium-based cation may be selected from 1-butyl-3-methylimidazolium [BMim] + 、1-ethyl-3-methylimidazolium cation [EMim] + 、1-Methylimidazolium cation [HMim] + 、1-Butyl imidazolium cation [HBim] + and mixtures thereof. For example, the imidazolium-based cation may be selected from 1-butyl-3-methylimidazolium [BMim] + 、1-Methylimidazolium cation [HMim] + 、1-Butyl imidazolium cation [HBim] + and mixtures thereof, such as 1-methylimidazolium cation [HMim] + 、1-Butyl imidazolium cation [HBim] + In one embodiment, the imidazolium-based cation is selected from 1-butyl-3-methylimidazolium [BMim] + 、1-Butyl imidazolium cation [HBim] + and mixtures thereof.
[0080] In some embodiments, the cations include proton alkylammonium, proton methylimidazolium, proton pyridinium, non-proton tetraalkylammonium, and non-proton dialkylimidazolium ions.
[0081] The ionic liquid may preferably be N,N-dimethylbutylammonium hydrogen sulfate ([DMBA][HSO4]), 1-butylimidazolium hydrogen sulfate ([HBim][HSO4]), triethylammonium hydrogen sulfate ([TEA][HSO4]), N-methylbutylammonium hydrogen sulfate ([MBA][HSO4]), 1-methylimidazolium formate ([HMim][HCOO]), N,N-dimethylbutylammonium formate ([DMBA][HCOO]) or a mixture thereof.
[0082] In one embodiment, the ionic liquid is not 1-ethyl-3-methylimidazolium acetate [EMim][OAc].
[0083] In another embodiment, the ionic liquid is selected from triethylammonium hydrogen sulfate [TEA][HSO4], N,N-dimethylbutylammonium hydrogen sulfate [DMBA][HSO4], diethylammonium hydrogen sulfate [DEA][HSO4], N,N-dimethylethylammonium hydrogen sulfate ([DMEA][HSO4]), diethanolammonium chloride [DEtOHA]Cl, 1-methylimidazolium hydrochloride [HMim]Cl, 1-ethyl-3-methylimidazolium chloride [EMim]Cl and 1-ethyl-3-methylimidazolium trifluoromethanesulfonate [EMim][OTf].
[0084] In another embodiment, the ionic liquid is selected from 1-butyl-3-methylimidazolium methyl sulfate [BMim][MeSO4], 1-butyl-3-methylimidazolium hydrogen sulfate [BMim][HSO4], 1-butyl-3-methylimidazolium methanesulfonate [BMim][MeSO3], 1-butylimidazolium hydrogen sulfate [HBim][HSO4] and 1-ethyl-3-methylimidazolium acetate [EMim][MeCO2].
[0085] Preferred ionic liquids are [alkylammonium][HSO4] ionic liquids, such as N,N-dimethylbutylammonium hydrogen sulfate ([DMBA][HSO4]), triethylammonium hydrogen sulfate ([TEA][HSO4]), N-methylbutylammonium hydrogen sulfate ([MBA][HSO4]), diethylammonium hydrogen sulfate [DEA][HSO4], N,N-dimethylethylammonium hydrogen sulfate ([DMEA][HSO4]) and ethylammonium hydrogen sulfate [ethylNH3][HSO4].
[0086] The stock solution solvent mentioned herein comprises an ionic liquid and optionally water. For use in the method disclosed herein, an ionic liquid is provided so that the stock solution solvent can dissolve lignin. Preferably, the solubility of cellulose in the stock solution solvent is lower than the solubility of lignin. More preferably, the stock solution solvent does not dissolve cellulose.
[0087] Ionic liquids (optionally mixed with water) can be used to treat lignocellulosic biomass, for example to separate lignin and cellulose, thereby preparing spinning solution in an integrated spinning process. The ionic liquid can dissolve the lignin in the biomass without dissolving the cellulose, so that the treatment produces cellulose pulp and lignin solution. Therefore, most of the cellulose remains solid, for example at least 70%, preferably at least 80% (wt% relative to the oven dry weight of the biomass). The cellulose pulp can be easily removed mechanically from the lignin solution, for example by filtering. Other components (such as hemicellulose) can also be dissolved in the ionic liquid.
[0088] When the ionic liquid is present in a mixture with water, this can be expressed as [ionic liquid] x% / water y% , where the percentage is the mass of the component relative to the total mass of the mixture (i.e., w / w %). For example, [DMBA][HSO4] 95% / water 5% Refers to a mixture of [DMBA][HSO4] and water, wherein [DMBA][HSO4] is present at 95% (w / w) (95 wt%) and water is present at 5% (w / w) (5 wt%).
[0089] Ionic liquids can be prepared by methods known to those skilled in the art or obtained commercially. For example, protonic ammonium-based ionic liquids can be made from simple alkylamines (such as triethylamine) and sulfuric acid in a one-step synthesis, such as described in George et al., (2015) "Design of low-cost ionic liquids for lignocellulosic biomass treatment" Green Chemistry 17: 1728-173.
[0090] Typically in an ionic liquid, the cation and anion are present in equimolar amounts. However, the ionic liquid may contain an excess of base, preferably a protonated base. 'Base' as used herein refers to a base from which the cation is derived, such as an amine / imidazole. The ionic liquid may contain a 10% molar excess of base, such as a 4-8%, 5-7.5% excess of base. The ionic liquid may contain a 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10% molar excess of base.
[0091] In another embodiment, the stock solution solvent further comprises 0.01-20% molar excess of acid, preferably 1-5% molar excess of acid, based on the percentage of the ionic liquid. The acid can be selected from any known strong acid, such as hydrochloric acid, sulfuric acid, nitric acid, hydroiodic acid, perchloric acid and hydrobromic acid. Preferably, the acid is sulfuric acid, or hydrochloric acid or phosphoric acid. More preferably, the acid is the same acid as the acid used to synthesize the protic ionic liquid.
[0092] It should be understood that features described throughout this disclosure may exist in any combination mutatis mutandis. For example, wherever a discussion of components or component loadings of a spinning solution is provided, these components may exist in any combination, and the loadings may exist in any combination.
[0093] All publications, published patent documents, and patent applications cited herein are hereby incorporated by reference to the same extent as if each individual publication, published patent document, or patent application was specifically and individually indicated to be incorporated by reference.
[0094] definition
[0095] In order to make the present invention more easily understood, certain terms are first defined below. Additional definitions for the following terms and other terms are set forth throughout the specification.
[0096] As used herein, the singular forms "a", "an", and "the" also include the plural forms unless the context clearly dictates otherwise. The use of the singular includes the plural unless clearly stated otherwise. As used herein, wherever "comprising" is mentioned, the term may also refer to "consisting essentially of" and "consisting of". For example, a stock solvent comprising an ionic liquid, water, and optionally ethanol may also be a stock solvent consisting essentially of an ionic liquid, water, and optionally ethanol.
[0097] As mentioned herein, "solvent" is a solvent in which lignin can be dissolved. The solvent can comprise a mixture of solvents. The solvent comprises an ionic liquid and optionally water. The solvent can comprise another solvent, such as ethanol. All solvents present in the spinning solution can constitute the solvent (that is, the spinning solution does not contain any solvent other than the solvent). The solvent can be substantially composed of an ionic liquid, water and optionally ethanol. Preferably, the solvent does not dissolve cellulose.
[0098] Various components are described as being present in the spinning solution with a certain percentage loading. Loading capacity is mass loading capacity, and the mass loading capacity can be referred to as loading capacity % or loading capacity wt%. In general, loading capacity is described as relative to the mass of the spinning solution, excluding the mass of lignin and carbon nano material. The loading capacity of the spinning solution components (i.e., lignin or carbon nano material) is calculated as:
[0099] (mass of component / mass of spinning solution excluding the mass of lignin and carbon nanomaterials) x 100
[0100] In embodiments where the spinning dope consists essentially of dope solvent (water, ionic liquid and optionally ethanol), lignin and carbon nanomaterial, the loading is calculated as:
[0101] (mass of component / solvent of stock solution) x 100
[0102] As described herein, in some embodiments, the spinning solution may contain additional solutes. In such embodiments, the loading amount is calculated as:
[0103] (mass of component / stock solvent + additional solute) x 100
[0104] As used herein, a "coagulant" is a liquid into which the spinning dope can be extruded. Extruding the spinning dope into the coagulant results in fiber formation.
[0105] Nanomaterials can be defined as materials having at least one external dimension of 100 nm or less. Carbon nanomaterials include, but are not limited to, carbon nanotubes, graphene nanoribbons, graphene nanoplates, and graphene nanosheets. Carbon nanotubes can be single-walled carbon nanotubes or multi-walled carbon nanotubes. Using carbon nanomaterials in the fiber production method described herein can provide improved spinning rheology, provide improved precursor fiber strength for ease of processing, provide improved graphite microstructure after conversion (potentially lower temperature conversion), and directly enhance the final carbon fiber.
[0106] As used herein, the term "lignocellulosic biomass" refers to living or dead biological material and can include any cellulose or lignocellulosic material, including materials comprising cellulose and optionally further comprising hemicellulose, lignin, starch, oligosaccharides and / or monosaccharides, biopolymers, natural derivatives of biopolymers, their mixtures and decomposition products. The term can also include other components, such as protein and / or lipid. Biomass can be derived from a single source, or the biomass can include a mixture derived from more than one source. Some specific examples of biomass include but are not limited to bioenergy crops, agricultural residues, municipal solid waste, industrial solid waste, paper sludge, yard waste, wood and forestry waste. Additional examples of biomass include, but are not limited to, corn kernels, corn cobs, crop residues (e.g., corn husks, corn stover), grasses (including Miscanthus X giganteus), wheat, wheat straw, hay, rice straw, switchgrass, waste paper, bagasse, sorghum, soybeans, components obtained from grinding grains, trees (e.g., pine trees), branches, roots, leaves, wood chips, wood pulp, sawdust, shrubs and bushes, vegetables, fruits, flowers, animal manure, multi-component feeds, and crustacean biomass (i.e., chitinous biomass). It may be preferred that the biomass be treated prior to use in the methods of the present invention. For example, the biomass may be mechanically treated, such as grinding or chopping.
[0107] As mentioned herein, "aging" of spinning solution refers to the time period before the spinning solution is extruded after the spinning solution has been prepared. During aging, the solution can remain at room temperature or can be heated. During aging, the solution can experience mixing. Aging can occur for at least 5 minutes, at least 30 minutes, for example, at most 72 hours or 48 hours.
[0108] Room temperature as mentioned herein may refer to 25°C.
[0109] As used herein, the term "aliphatic" refers to a straight or branched chain hydrocarbon that is fully saturated or contains one or more unsaturated units. Thus, an aliphatic may be an alkyl, alkenyl or alkynyl group, preferably having from 1 to 12 carbon atoms, preferably having up to 6 carbon atoms or more preferably up to 4 carbon atoms. An aliphatic may have 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12 carbon atoms.
[0110] As used herein, the term "alkyl" is typically a straight or branched chain alkyl group or moiety containing 1 to 20 carbon atoms, such as 11, 12, 13, 14, 15, 16, 17, 18 or 19 carbon atoms. Preferably, the alkyl group or moiety contains 1-10 carbon atoms, i.e., 2, 3, 4, 5, 6, 7, 8, 9 or 10 carbon atoms, such as C1-4 Alkyl or C 1-6 Alkyl or moiety such as methyl, ethyl, n-propyl, isopropyl, n-, iso- and tert-butyl, n-pentyl, methylbutyl, dimethylpropyl, n-hexyl, 2-methylpentyl, 3-methylpentyl, 2,3-dimethylbutyl and 2,2-dimethylbutyl.
[0111] As used herein, the term "carbocycle" refers to a saturated or partially unsaturated cyclic group having 3 to 6 ring carbon atoms (i.e., 3, 4, 5 or 6 carbon atoms). The carbocycle is preferably a "cycloalkyl", which, as used herein, refers to a fully saturated hydrocarbon ring group. Preferably, the cycloalkyl is a C3-C6 cycloalkyl.
[0112] The term "C 6-10 "Aryl" means an aromatic group consisting of 6, 7, 8, 9 or 10 carbon atoms, and includes condensed ring groups such as monocyclic groups or bicyclic groups. Specifically, "C 6-10 Examples of "aryl" include phenyl, indenyl, naphthyl or azulenyl, etc. It should be noted that condensed rings such as indane and tetrahydronaphthalene are also included in the aryl group.
[0113] As used herein, the term "alkaryl" refers to an alkyl group as defined below substituted by an aryl group as defined above. The alkyl component of an "alkaryl" group may be substituted with any one or more of the substituents listed above for aliphatic groups, and the aryl or heteroaryl components of an "alkaryl" or "alkylheteroaryl" group may be substituted with any one or more of the substituents listed above for aryl and carbocyclic groups. Preferably, the alkaryl group is benzyl.
[0114] As used herein, the term "heteroaryl" refers to a monocyclic or bicyclic aromatic ring system having 5 to 10 ring atoms (i.e., 5, 6, 7, 8, 9 or 10 ring atoms), at least one ring atom being a heteroatom selected from O, N or S.
[0115] As mentioned herein, the aliphatic, aryl, heteroaryl or carbocyclic groups may be unsubstituted or may be substituted by one or more substituents independently selected from the group consisting of halo, C 1-6 Alkyl, -NH2, -NO2, -SO3H, –OH, alkoxy, -COOH, or –CN.
[0116] The term "halogen atom" or "halo" used herein refers to a fluorine atom, a chlorine atom, a bromine atom, an iodine atom or the like, preferably a fluorine atom or a chlorine atom, and more preferably a fluorine atom.
[0117] “C 2-6 "Alkoxy" refers to the above C 1-6Alkyl, the oxygen is also bonded to the cationic ring. 2-6 "Alkoxyalkyl" refers to an alkyl group containing an ether group having the general formula XOY, wherein X and Y are each independently C 1-5 The total number of carbon atoms is between 2 and 6, for example 2, 3, 4, 5 or 6.
[0118] As used herein, the term "alkenyl" refers to a straight or branched chain alkenyl or moiety containing 2 to 20 carbon atoms, such as 11, 12, 13, 14, 15, 16, 17, 18 or 19 carbon atoms. Preferably, the alkenyl or moiety contains 2-10 carbon atoms, i.e., 2, 3, 4, 5, 6, 7, 8, 9 or 10 carbon atoms, such as C 2-4 Alkenyl or C 2-6 Alkenyl or moiety, for example, ethenyl, 1-propenyl, 2-propenyl, 1-butenyl, 2-butenyl, 3-butenyl, 1-pentenyl, 2-pentenyl, 3-pentenyl, 4-pentenyl, 1-hexenyl, 2-hexenyl, 3-hexenyl, 4-hexenyl, and 5-hexenyl.
[0119] As used herein, the term "alkynyl" refers to a straight or branched chain alkynyl group or moiety containing 2 to 20 carbon atoms, such as 11, 12, 13, 14, 15, 16, 17, 18 or 19 carbon atoms. Preferably, the alkynyl group or moiety contains 2-10 carbon atoms, i.e., 2, 3, 4, 5, 6, 7, 8, 9 or 10 carbon atoms, such as C 2-4 Alkynyl or C 2-6 Alkynyl or moiety, for example, ethynyl, 1-propynyl, 2-propynyl, 1-butynyl, 2-butynyl, 3-butynyl, 1-pentynyl, 2-pentynyl, 3-pentynyl, 4-pentynyl, 1-hexynyl, 2-hexynyl, 3-hexynyl, 4-hexynyl and 5-hexynyl.
[0120] The present disclosure provides aspects and embodiments as set out in the following clauses:
[0121] 1. A method for producing a fiber, the method comprising:
[0122] Providing a spinning solution, the spinning solution comprising a solution solvent, lignin dissolved in the solution solvent, and a carbon nanomaterial, wherein the solution solvent comprises an ionic liquid and optionally water; and
[0123] The spinning solution is extruded into a coagulant to obtain one or more fibers.
[0124] 2. The method according to clause 1, wherein the water content of the stock solution solvent is 0-30 wt%.
[0125] 3. The method according to clause 1 or 2, wherein the water content of the stock solution solvent is 0-20 wt%.
[0126] 4. The method according to any one of the preceding clauses, wherein the water content of the stock solution solvent is 0-15 wt%.
[0127] 5. The method according to any one of the preceding clauses, wherein the water content of the stock solution solvent is 0-10 wt%.
[0128] 6. The method according to any one of the preceding clauses, wherein the water content of the stock solution solvent is 0-5 wt%.
[0129] 7. A method according to any of the preceding clauses, wherein the stock solution solvent comprises at least 1 wt% water.
[0130] 8. A method according to any one of the preceding clauses, wherein the stock solution solvent comprises at least 2 wt% water.
[0131] 9. A method according to any of the preceding clauses, wherein the stock solution solvent comprises at least 3 wt% water.
[0132] 10. The method according to any of the preceding clauses, wherein the lignin is present in a loading of at least 5 wt% relative to the total mass of the spinning solution, excluding the mass of lignin and carbon nanomaterial.
[0133] 11. The method according to clause 10, wherein the lignin is present at a loading of at least 10 wt%.
[0134] 12. The method according to clause 11, wherein the lignin is present in a loading of 10-50 wt.
[0135] 13. The method according to clause 12, wherein the lignin is present in a loading of 10-40 wt.
[0136] 14. The method according to clause 13, wherein the lignin is present at a loading of 10-30 wt%.
[0137] 15. The method according to any of the preceding clauses, wherein the carbon nanomaterial is present in a loading of at least 0.001 wt% relative to the mass of the spinning solution, excluding the mass of lignin and carbon nanomaterial.
[0138] 16. The method of clause 15, wherein the carbon nanomaterial is present at a loading of at least 0.01 wt%.
[0139] 17. The method according to clause 16, wherein the carbon nanomaterial is present in a loading amount of at least 0.01 wt%.
[0140] 18. The method according to clause 17, wherein the carbon nanomaterial is present at a loading of 0.001-10 wt%.
[0141] 19. The method according to clause 18, wherein the carbon nanomaterial is present at a loading of 0.001-8 wt%.
[0142] 20. The method according to clause 19, wherein the carbon nanomaterial is present at a loading of 0.01-8 wt%.
[0143] 21. The method according to clause 20, wherein the carbon nanomaterial is present at a loading of 0.1-5 wt%.
[0144] 22. The method according to clause 21, wherein the carbon nanomaterial is present at a loading of 0.1-1 wt%.
[0145] 23. The method according to clause 22, wherein the carbon nanomaterial is present at a loading of 0.3-0.7 wt%.
[0146] 24. The method according to any one of the preceding clauses, wherein the weight ratio of lignin to carbon nanomaterial in the spinning solution is 5:1 to 10000:1.
[0147] 25. The method according to any one of the preceding clauses, wherein the weight ratio of lignin to carbon nanomaterial in the spinning solution is from 5:1 to 5000:1.
[0148] 26. The method according to any one of the preceding clauses, wherein the weight ratio of lignin to carbon nanomaterial in the spinning solution is from 10:1 to 1000:1.
[0149] 27. The method according to any one of the preceding clauses, wherein the weight ratio of lignin to carbon nanomaterial in the spinning solution is from 20:1 to 200:1.
[0150] 28. A method according to any one of the preceding clauses, wherein the carbon nanomaterial is dispersed in the stock solution solvent.
[0151] 29. The method according to any of the preceding clauses, wherein the carbon nanomaterial comprises carbon nanotubes, carbon nanoribbons, graphene nanoplates or a combination thereof.
[0152] 30. The method of clause 29, wherein the carbon nanomaterial comprises carbon nanotubes.
[0153] 31. The method of clause 30, wherein the carbon nanotubes are single-walled carbon nanotubes (SWCNTs).
[0154] 32. A method according to any of the preceding clauses, wherein the ionic liquid comprises a cation and an anion, wherein the anion is selected from C 1-20 Alkyl sulfate ion ([alkyl SO4] - ), C 1-20 Alkylsulfonate ion ([alkylSO3] - ), bisulfate ion ([HSO4] - ), bisulfite ion ([HSO3] - ), dihydrogen phosphate ion ([H2PO4] - ), hydrogen phosphate ion ([HPO4] 2- ), chloride ion (Cl - ), bromide ion (Br - ), trifluoromethanesulfonate ion ([oTf] - ), formate ion ([HCOO] - ) and acetate ions ([MeCO2] - ).
[0155] 33. The method according to clause 32, wherein the anion is selected from [HSO4] - and [HCOO] - .
[0156] 34. A method according to any of the preceding clauses, wherein the ionic liquid comprises a cation and an anion, wherein the cation is a protic cation.
[0157] 35. A method according to any of the preceding clauses, wherein the ionic liquid comprises a cation and an anion, wherein the cation contains a nitrogen-containing heterocyclic moiety, or wherein the cation is a cation of formula I:
[0158]
[0159] Among them A 1 To A 4 Each independently selected from H, aliphatic, C 3-6 Carbon ring, C 6-10 Aryl, alkaryl and heteroaryl.
[0160] 36. A method according to any of the preceding clauses, wherein the ionic liquid is an [alkylammonium][HSO4] or [alkylammonium][HCOO] ionic liquid.
[0161] 37. A method according to any of the preceding clauses, wherein the ionic liquid is triethylammonium hydrogen sulfate [TEA][HSO4], N,N-dimethylbutylammonium hydrogen sulfate [DMBA][HSO4], diethylammonium hydrogen sulfate [DEA][HSO4], N,N-dimethylethylammonium hydrogen sulfate ([DMEA][HSO4]), diethanolammonium chloride [DEtOHA] Cl, 1-methylimidazolium hydrochloride [HMim] Cl, 1-ethyl-3-methylimidazolium chloride [EMim] Cl and 1-ethyl-3-methylimidazolium trifluoromethanesulfonate [EMim][OTf], 1-butylimidazolium hydrogen sulfate ([HBim][HSO4]), methylbutylammonium hydrogen sulfate ([MBA][HSO4]), 1-methylimidazolium formate ([HMim][HCOO]), N,N-dimethylbutylammonium formate ([DMBA][HCOO]), N,N-dimethylethylammonium hydrogen sulfate ([DMEA][HSO4]), 1-butyl-3-methylimidazolium hydrogen sulfate [BMim][HSO4] or N-dimethylbutylammonium acetate ([DMBA][OAc]) or a mixture thereof.
[0162] 38. A method according to any of the preceding clauses, wherein the ionic liquid is N,N-dimethylethylammonium hydrogen sulfate ([DMEA][HSO4]), N,N-dimethylbutylammonium hydrogen sulfate ([DMBA][HSO4]), 1-butylimidazolium hydrogen sulfate ([HBim][HSO4]), triethylammonium hydrogen sulfate ([TEA][HSO4]), methylbutylammonium hydrogen sulfate ([MBA][HSO4]), 1-methylimidazolium formate ([HMim][HCOO]), N,N-dimethylbutylammonium formate ([DMBA][HCOO]), 1-methylimidazolium hydrogen chloride [HMim]Cl, N,N-dimethylbutylammonium chloride [DMBA]Cl, 1-butyl-3-methylimidazolium hydrogen sulfate [BMim][HSO4] or N-dimethylbutylammonium acetate ([DMBA][oAc]) or a mixture thereof.
[0163] 39. A method according to any of the preceding clauses, wherein the ionic liquid is N,N-dimethylbutylammonium hydrogen sulfate ([DMBA][HSO4]), 1-butylimidazolium hydrogen sulfate ([HBim][HSO4]), triethylammonium hydrogen sulfate ([TEA][HSO4]), methylbutylammonium hydrogen sulfate ([MBA][HSO4]), 1-methylimidazolium formate ([HMim][HCOO]), N,N-dimethylbutylammonium formate ([DMBA][HCOO]), 1-methylimidazolium hydrogen chloride [HMim]Cl, N,N-dimethylbutylammonium chloride [DMBA]Cl, 1-butyl-3-methylimidazolium hydrogen sulfate [BMim][HSO4] or N-dimethylbutylammonium acetate ([DMBA][OAc]) or a mixture thereof.
[0164] 40. A method according to any of the preceding clauses, wherein the ionic liquid is N,N-dimethylbutylammonium hydrogen sulfate ([DMBA][HSO4]), 1-butylimidazolium hydrogen sulfate ([HBim][HSO4]), triethylammonium hydrogen sulfate ([TEA][HSO4]), methylbutylammonium hydrogen sulfate ([MBA][HSO4]), 1-methylimidazolium formate ([HMim][HCOO]) or N,N-dimethylbutylammonium formate ([DMBA][HCOO]) or a mixture thereof.
[0165] 41. A method according to any of the preceding clauses, wherein the ionic liquid is [DMBA]Cl, [DMBA][HSO4], [BMim][HSO4], [MBA][HSO4] or [HBim][HSO4] or a mixture thereof.
[0166] 42. A method according to any of the preceding clauses, wherein the ionic liquid is [DMBA][HSO4].
[0167] 43. A method according to any of the preceding clauses, wherein the stock solution solvent further comprises ethanol.
[0168] 44. The method according to clause 43, wherein the ethanol is present in 1-20 wt% of the stock solvent relative to the total weight of the stock solvent.
[0169] 45. A method according to clause 44, wherein the ethanol is present at 5-15 wt%.
[0170] 46. A process according to any one of clauses 43 to 45, wherein the mass ratio of ionic liquid:ethanol is from 3:1 to 15:1.
[0171] 47. A process according to any one of clauses 43 to 46 wherein the mass ratio of ionic liquid:ethanol is from 5:1 to 12:1.
[0172] 48. A method according to any of the preceding clauses, wherein the water content of the spinning solution is at least 5 wt%, and the water content is calculated based on the mass of water present relative to the mass of the spinning solution, excluding the mass of lignin and carbon nanomaterial.
[0173] 49. A method according to any of the preceding clauses, wherein the water content of the spinning solution is 5-40 wt%, and the water content is calculated based on the mass of water present relative to the mass of the spinning solution, excluding the mass of lignin and carbon nanomaterials.
[0174] 50. A method according to any of the preceding clauses, wherein the water content of the spinning solution is 10-40 wt%, and the water content is calculated based on the mass of water present relative to the mass of the spinning solution, excluding the mass of lignin and carbon nanomaterials.
[0175] 51. A method according to any of the preceding clauses, wherein the water content of the spinning solution is 20-40 wt%, and the water content is calculated based on the mass of water present relative to the mass of the spinning solution, excluding the mass of lignin and carbon nanomaterials.
[0176] 52. A method according to any of the preceding clauses, wherein the coagulant comprises water.
[0177] 53. A method according to any of the preceding clauses, wherein the coagulant comprises water and an ionic liquid, wherein the ionic liquid is present in no more than 60 wt% relative to the total mass of the coagulant.
[0178] 54. A method according to any of the preceding clauses, wherein the coagulant comprises water and an ionic liquid, wherein the ionic liquid is present in no more than 30 wt% relative to the total mass of the coagulant.
[0179] 55. A method according to any of the preceding clauses, wherein the coagulant comprises water and an ionic liquid, wherein the ionic liquid is present in no more than 15 wt% relative to the total mass of the coagulant.
[0180] 56. A method according to any of the preceding clauses, wherein the coagulant comprises water and an ionic liquid, wherein the ionic liquid is present in 1-60 wt% relative to the total mass of the coagulant.
[0181] 57. A method according to any of the preceding clauses, wherein the coagulant comprises water and an ionic liquid, wherein the ionic liquid is present in 1-30 wt% relative to the total mass of the coagulant.
[0182] 58. A method according to any of the preceding clauses, wherein the coagulant comprises water and an ionic liquid, wherein the ionic liquid is present in 1-15 wt% relative to the total mass of the coagulant.
[0183] 59. The method according to any of the preceding clauses, wherein the coagulant comprises water and an ionic liquid, wherein the ionic liquid is present in 5-15 wt% or 5-10 wt% relative to the total mass of the coagulant.
[0184] 60. A method according to any of the preceding clauses, wherein the coagulant comprises water and sodium sulfate.
[0185] 61. A method according to clause 60, wherein the coagulation bath comprises an aqueous solution of sodium sulfate having a concentration of 0.5-1.5 M.
[0186] 62. The method according to any of the preceding clauses, wherein providing the spinning solution comprises:
[0187] a) dissolving lignin in a stock solvent to obtain a lignin solution;
[0188] b) combining the lignin solution with a carbon nanomaterial; and
[0189] c) dispersing the carbon nanomaterial in the dope solvent to obtain a spinning dope, optionally by shearing.
[0190] 63. The method according to clause 62, wherein the dissolution of the lignin is carried out at a temperature of 10°C to 100°C.
[0191] 64. The method according to clause 63, wherein the dissolution of the lignin is carried out at a temperature of 20°C to 60°C.
[0192] 65. The method according to clause 64, wherein the dissolution of the lignin is carried out at a temperature of 20°C to 30°C.
[0193] 66. A method according to any of the preceding clauses, wherein the spinning solution is prepared by a method comprising preparing a lignin solution and combining the lignin solution with the carbon nanomaterial.
[0194] 67. The method according to clause 66, wherein the lignin solution is prepared by:
[0195] a) contacting a lignocellulosic biomass comprising lignin and cellulose with a composition comprising an ionic liquid and water to dissolve the lignin and produce a cellulose pulp;
[0196] b) separating the cellulose pulp to obtain a mother liquor comprising the ionic liquid, water and lignin; and
[0197] c) optionally adjusting the amount of ionic liquid and / or water in the mother liquor to obtain the lignin solution.
[0198] 68. The method of clause 62, 66 or 67, further comprising aging the lignin solution for at least 2 minutes prior to combining with the carbon nanomaterial.
[0199] 69. The method of clause 62, 66 or 67, further comprising aging the lignin solution for at least 5 minutes prior to combining with the carbon nanomaterial.
[0200] 70. The method of clause 62, 66 or 67, further comprising aging the lignin solution for at least 30 minutes prior to combining with the carbon nanomaterial.
[0201] 71. The method of clause 62, 66 or 67, further comprising aging the lignin solution for at least 1 hour prior to combining with the carbon nanomaterial.
[0202] 72. The method of clause 62, 66 or 67, further comprising aging the lignin solution for at least 1 day prior to combining with the carbon nanomaterial.
[0203] 73. The method of clause 62, 66 or 67, further comprising aging the lignin solution for at least 5 days prior to combining with the carbon nanomaterial.
[0204] 74. The method of clause 62, 66 or 67, further comprising aging the lignin solution for at least 10 days prior to combining with the carbon nanomaterial.
[0205] 75. The method according to any one of clauses 68 to 74, wherein the lignin solution is heated at a temperature of at least 30°C during aging.
[0206] 76. The method according to any one of clauses 68 to 74, wherein the lignin solution is heated at a temperature of at least 60°C during aging.
[0207] 77. The method according to any one of clauses 68 to 76, wherein the lignin solution is heated at a temperature of at most 150°C during aging.
[0208] 78. The method according to any one of clauses 67 to 77, wherein the composition comprising the ionic liquid and water has a water content of 2-40 wt%.
[0209] 79. The method according to clause 78, wherein the composition comprising the ionic liquid and water has a water content of 5-40 wt%.
[0210] 80. The method according to clause 79, wherein the composition comprising the ionic liquid and water has a water content of 5-10 wt%.
[0211] 81. The method of any one of clauses 67 to 80, wherein the lignocellulosic biomass contacted with the composition is heated to 100-180°C.
[0212] 82. The method of any one of clauses 67 to 80, wherein the lignocellulosic biomass contacted with the composition is heated to 120-170°C.
[0213] 83. The method of any one of clauses 67 to 80, wherein the lignocellulosic biomass contacted with the composition is heated to 120-150°C.
[0214] 84. The method of any one of clauses 67 to 83, wherein the lignocellulosic biomass is contacted with the composition for a period of from 1 minute to 22 hours.
[0215] 85. The method of any one of clauses 67 to 83 wherein the lignocellulosic biomass is contacted with the composition for 10 minutes to 22 hours.
[0216] 86. A method according to any one of clauses 67 to 83 wherein the lignocellulosic biomass is contacted with the composition for 10 minutes to 10 hours.
[0217] 87. The method of any one of clauses 67 to 83 wherein the lignocellulosic biomass is contacted with the composition for 15 minutes to 8 hours.
[0218] 88. The method of any one of clauses 67 to 83 wherein the lignocellulosic biomass is contacted with the composition for 30 minutes to 8 hours.
[0219] 89. A method according to any of the preceding clauses, further comprising drying the one or more fibers under mechanical tension.
[0220] 90. A method according to any of the preceding clauses, further comprising heating the one or more fibers in air.
[0221] 91. The method of clause 90, comprising heating the one or more fibers in air at 150-300°C.
[0222] 92. The method according to any of the preceding clauses, further comprising carbonizing the one or more fibers to obtain carbon fibers.
[0223] 93. The method of clause 92, wherein carbonizing comprises heating the one or more fibers to 800-3000°C under an inert atmosphere.
[0224] 94. The method of clause 93, wherein carbonizing comprises heating the one or more fibers to 1200-1800°C under an inert atmosphere.
[0225] 95. A method according to any of the preceding clauses, wherein the spinning solution comprises a cellulose loading of no more than 10 wt% relative to the mass of the spinning solution, excluding the mass of cellulose, lignin and carbon nanomaterials.
[0226] 96. A method according to any of the preceding clauses, wherein the cellulose loading of the spinning solution does not exceed 5 wt%.
[0227] 97. A method according to any of the preceding clauses, wherein the cellulose loading of the spinning solution does not exceed 4 wt%.
[0228] 98. A method according to any of the preceding clauses, wherein the cellulose loading of the spinning solution does not exceed 1 wt%.
[0229] 99. A fiber obtainable by a method according to any of the preceding clauses.
[0230] 100. A fiber obtained by a method according to any of the preceding clauses.
[0231] 101. A spinning solution comprising a solution solvent, lignin and a carbon nanomaterial, wherein the solution solvent comprises an ionic liquid and optionally water.
[0232] 102. A dispersion comprising carbon nanotubes and [DMBA][HSO4].
[0233] 103. The dispersion according to clause 102, wherein the dispersion is a dispersion of carbon nanotubes in any stock solvent as described in any of the preceding clauses, wherein the ionic liquid is [DMBA][HSO4].
[0234] The present invention will now be described with reference to the following examples and drawings, which are presented for illustrative purposes only and should not be construed as limiting the present invention.
[0235] Example
[0236] Material
[0237] Optical micrographs were visually observed on a Leica DM2500 optical microscope connected to a Basler camera and associated software to capture and process the images.
[0238] Single wall nanotubes (SWCNTs) were obtained from OCSiAl. TUBALL 75 (<2 nm diameter, >1 μm length, >15% metal impurities). TUBALL 99 (>2 nm diameter, >5 μm length, <1% metal impurities).
[0239] Eucalyptus biomass (Eucalytpus grandis), a hardwood lignin, was obtained from WL West & sons Ltd. Ethanol (anhydrous) was purchased from VWR.
[0240] Lignin extraction was performed following the ionoSolv pretreatment procedure (Gschwend, FJv et al. Journal of Visualized Experiments 2016, 2016(114), 4–9).
[0241] method
[0242] Example 1: Ionic Liquid Synthesis
[0243] The ionic liquid [DMBA][HSO4] was synthesized in a custom flow reactor from N,N-dimethylbutylamine and 66.3% sulfuric acid solution. All reagents were used as received. The precursor was cooled and pumped into a stirred flow reactor at a flow rate of 5 ml / min for acid and 7.8 ml / min for base. The acid / base ratio of the produced ionic liquid was checked in triplicate using an automatic titrator (Mettler Toledo G205), where HSO4 was titrated with aqueous NaOH. - To correct the acid / base ratio, a calculated amount of DMBA or 66.3% sulfuric acid was gradually added to the ionic liquid cooled in an ice bath.
[0244] The water content of the ionic liquid was measured using a volumetric Karl Fischer titrator (Mettler-Toledo). The initial water content of the ionic liquid was determined to be 4.22%. The water content was adjusted as needed by adding more water, with the desired water content being 4.74-5%. [DMBA][HSO4] 95% / water 5% It will be denoted as DH5. Lignin (12 wt%) dissolved in DH5 will be denoted as lig-DH5.
[0245] Example 2: SWCNT dispersion in DH5
[0246] 1) SWCNT (2 mg, TUBALL 99% purity) was added to a mortar (marble). The ionic liquid water mixture (DH5, 200 mg) was drawn into a syringe and added dropwise, starting with a minimum of two drops (38 mg). Transfer losses may occur in the syringe, so the weight of the syringe was recorded on a balance after each addition, and the added mass of DH5 was calculated according to equation 1.
[0247] 2) A minimum amount of DH5 (38 mg) was ground with SWCNTs (5.2 wt%) using a pestle for 7-10 minutes, applying high shear to break up large aggregates until a smooth paste was formed. The mixture was ground for a total of 30 minutes.
[0248] 3) A small amount of the dispersion was placed on a labeled glass slide and covered with a cover slip for analysis by optical microscopy (OM).
[0249] Equation 1
[0250] Dispersions of SWCNTs in [DMBA][HSO4] at various concentrations were prepared. Dispersions of SWCNTs in [DMBA][HSO4] provided different sample textures at concentrated and diluted concentrations. The consistency (15 min shear) of the 5.2 wt% dispersion was similar to a dry smooth solid that retained its shape when cut in half. In contrast, the diluted samples containing 1.3 wt% and 0.5 wt% SWCNTs resembled a gel or soft solid. When placed on a slide for analysis by OM, they formed a wet paste and a gray film.
[0251] High purity pristine SWCNTs (TUBALL 99) were dispersed in DH5 to provide a uniform and thorough dispersion without large aggregates under optimized conditions.
[0252] Rheology
[0253] It was found that the viscosity of the SWCNT dispersion in DH5 decreased when the shear rate was increased (shear thinning, Figure 1Results are shown for SWCNT dispersions at 0.25 wt%, 0.5 wt% and 1 wt% SWCNTs.) Shear thinning is caused by disentanglement or alignment of dissolved and dispersed materials in the flow and can be beneficial in creating alignment in the textile fibers, which in turn can produce an improved graphitic structure in the resulting carbon fibers.
[0254] The viscosity of SWCNT dispersions was measured using an AR 2000ex rheometer with a cone-plate feature (2 ° cone angle, 20 mm plate diameter and 53 μm gap). Dynamic stability, strain and time sweep measurements were performed at 25 ° C (RT). The stability of the gel / stock solution was measured for more than 30 minutes at a constant strain of 1.5% and a frequency of 0.1 radian / second. Immediately thereafter, a strain sweep was performed to identify the linear viscoelastic region (LVR), where the strain % was set to 0.1% to 1000% at an angular frequency of 10 radian / second. The LVR of all gels was identified as approximately 1-2%, and therefore a frequency sweep was performed at 1.5% strain to identify the dominant behavior of the gel / stock solution over a frequency range of 0.1-100 radian / second.
[0255] Zero shear rate viscosity was measured at room temperature using an AR2000ex rheometer with cone and plate features (2° cone angle, 20 mm plate diameter and 53 μm gap) at low shear rates from 3.00 x 10-6 to 30 s-1. For a 0.5 (w / w)% dispersion in DH5, the zero shear rate viscosity was measured at room temperature at 1.01 x 10 -4 -4.65x10 -4 s -1 Zero shear rate was recorded between 117,100-101,300 Pa.s at shear rates.
[0256] strain
[0257] The strain sweep identified the linear viscoelastic region (LVR) as 1.5-2% and the critical strain as 12-29% ( Figure 2 ). LVR enables the identification of the dominant behavior of the gel, characterized by the frequency sweep. It was found that the G' value (elastic behavior) increases with increasing concentration of SWCNTs, indicating the formation of an elastic network at higher concentrations ( Figure 3 , 1.0 wt %). All gels were found to be predominantly elastic (0.25 wt %, 0.5 wt % and 1.0 wt %).
[0258] Example 3: Preparation of composite material stock solution and wet spinning of lignin nanocomposite fibers
[0259] 1) To a flask equipped with a stir bar and ionic liquid solution DH5, add lignin to achieve a polymer loading of 12 wt%. Fix the flask over an oil / water bath, heat to 60°C and stir for 1.5 hours (900 RPM). Check the homogeneity of the solution by OM.
[0260] 2) Aspirate Lig-DH5 into a 1 ml syringe and record the weight. Add a minimum amount of lig-DH5 dropwise (50-70 mg) to a mortar containing SWCNTs (0.5 wt%, TUBALL 99). Shear the minimum amount of lig-DH5 and SWCNTs vigorously with a pestle for 15 minutes. Add the remaining mixture gradually over 30 minutes, applying high shear each time to disperse the SWCNTs to produce a lignin CNT composite stock solution. If the volume of SWCNTs increases (>4 mg), the shear time is extended.
[0261] 3) Once a good dispersion is obtained and observed by OM, the composite stock solution is drawn into a syringe. The composite stock solution is wet extruded into a rotating coagulation bath containing deionized water using a syringe pump (needle diameter can range from 24-27G, extrusion rate 0.009 ml / min). The fiber is allowed to coagulate for 15 minutes and carefully fixed on a drying table with adhesive tape. A foil weight (10-20 mg) is placed at the bottom of the fiber.
[0262] Lig-DH5 alone without additives was not spinnable in deionized (DI) water. In contrast, lignin was spinnable when SWCNTs were incorporated into the stock solution. Fibers containing lignin (96%) and SWCNTs (4%) were spun continuously and could retain their shape after coagulation in DI water for 30 minutes. SWCNTs were well dispersed in lig-DH5, and the fiber surface had areas of smooth texture and uniformity.
[0263] Thermogravimetric analysis (TGA) was performed to simulate the carbonization process that occurred with the precursor fibers. After drying overnight, the lignin CNT composite fibers were analyzed by TGA, which was performed on a Mettler-Toledo TGA / DSC 1LF / UMX. The samples were heated in a platinum pan at 10 °C for 10 min. -1 The mixture was heated from 25°C to 100°C with a nitrogen flow, maintained isothermally at 100°C for 30 minutes to drive off moisture, and the temperature was increased by 10°C min. -1 The temperature was raised to 900°C. The process was repeated in air. The results are shown in Figure 4 and 5 middle. Figure 5 Pyrolysis in N2 was shown to produce a carbon yield of 54.0%.
[0264] Example 4: Integration of lignin extraction and lignin fiber spinning
[0265] Biomass pretreatment (lignin extraction in [DMBA][HSO4])
[0266] Lignin extraction was performed following the ionoSolv pretreatment procedure (Gschwend, FJV et al. Journal of Visualized Experiments 2016, 2016(114), 4–9). 9 g or 12 g (oven dried basis, ODW) of biomass was added to a 100 mL pressure tube (Ace Glass, Vineland, NJ, USA, front sealing), followed by the addition of approximately 30 g of [DMBA][HSO4] 83% / water 17% To obtain a suspension with a biomass loading of 30% or 40% and a water content of 20%. Biomass and ionic liquid solutions are fully mixed with a vortex oscillator (VWR) until all biomass particles are in contact with the ionic liquid. The pressure tube is placed in a preheated 150°C oven for 1 hour. The mixture in the pressure tube is cooled and transferred to a 500mL glass bottle, then mixed with 180g of anhydrous ethanol (EtOH), fully shaken and left to stand at room temperature for 1 hour. After 1 hour, vacuum filtration is used to separate the mixture into a cellulose-rich solid and a liquid containing ionic liquid, ethanol and dissolved lignin (mother liquor). Cellulose is air-dried. The pulp is washed three more times with EtOH, followed by Soxhlet extraction in ethanol for 24 hours. Mother liquors are collected, and most of the water and EtOH are evaporated from the combined mother liquor fractions using a rotary evaporator. Lignin extraction is carried out in triplicate. The mother liquors obtained from the lignin extraction of 30% and 40% biomass loadings are labeled as mother liquor 30 and mother liquor 40.
[0267] Composition analysis of biomass and pulp
[0268] Composition analysis was performed according to the standard procedure published by the National Renewable Energy Laboratory (NREL) (Sluiter, A. et al., "National Renewable Energy Laboratory (Natl.Renew.Energy Lab.)" 2008, Issue: April 2008, 17). The extract was removed from the ground eucalyptus wood using EtOH using a Soxhlet extractor for 24 hours, and the extract content was quantified by measuring the weight difference. About 300 mg of air-dried extract-free biomass (based on oven dry weight, sieved to 180-850 μm) or recycled pulp was weighed into a 100 ml pressure tube (Ace Glass Company), and the exact weight was recorded. 3 mL of 72% sulfuric acid (Fluka) was added, the sample was stirred with a Teflon stirring rod, and the pressure tube was placed in a preheated water bath at 30 ° C. The sample was stirred again every 10 minutes for 1 hour. These samples were then diluted with 84 mL of distilled water and a lid was added. The sample was autoclaved at 121°C for 1 hour (SanyoLabo autoclave ML5 3020U) and allowed to cool to near ambient temperature. The sample was filtered through a filtering ceramic crucible of known weight. The filtrate was filled into two Falcon tubes (for acid-soluble lignin content and sugar content determination), and the black solid was washed with distilled water. The crucible containing acid-insoluble lignin and ash was dried at 105°C for 24 ± 2 hours in a convection oven (VWR Venti-Line115). Before recording the weight of the crucible, they were placed in a desiccator for 15 minutes. The crucible was placed in a muffle furnace (Nabertherm + controller P 330) and ashed to constant weight at 575°C. Before recording the weight of the crucible again, they were placed in a desiccator again for 15 minutes. The content of acid-insoluble lignin (AIL) is determined according to equation 1:
[0269]
[0270] Where W 坩埚加空气 is the weight of the acid-insoluble residue in the dried crucible, W 坩埚加灰分 It is the weight of the crucible after ashing to 575℃.
[0271] The acid soluble lignin content (ASL) was determined by UV analysis of the autoclaved filtrate at 286 nm (Perkin Elmer λ650 UV / Vis spectrometer). 200 μL of sample and 800 μL of DI water were added to a cuvette (dilution 1:4), mixed thoroughly and the absorbance A was recorded. ASL was calculated according to Equation 2:
[0272]
[0273] where A is the absorbance at 286 nm, l is the optical path length of the cuvette in cm (1 cm in this case), ε is the extinction coefficient (25 L / g cm), c is the concentration in mg / mL, ODW is the oven-dried weight of the sample in mg and V 滤液 is the volume of the filtrate in mL and is equal to 86.73 mL.
[0274] Calcium carbonate is added in the remaining filtrate until the solution pH reaches 5.Liquid is filtered through a 0.2 μm PTFE syringe filter and HPLC analysis is performed to determine total sugar content (Shimadzu, Aminex HPX-97P from Biorad, 300x7.8mm, pure water as mobile phase, with 0.6 ml / min, column temperature 85 ° C). Use concentrations of 0.1 mg / mL, 1 mg / mL, 2 mg / mL and 4 mg / mL glucose, xylose, mannose, arabinose and galactose calibration standards.Sugar recovery standards are made into 10 mL aqueous solutions close to the expected sugar concentration of the sample and transferred to a pressure tube.Add 278 μL 72% sulfuric acid, close the pressure tube and autoclave, and determine sugar content as described above.Determine the sugar recovery coefficient (SRC) and sugar content of the analytical sample according to equation 3 and equation 4 respectively:
[0275]
[0276] where c HPLC is the sugar concentration detected by HPLC, V is the initial volume of the solution in mL (10.00 mL for the sugar recovery standard and 86.73 mL for the sample), initial weight is the mass of sugar weighed, corr anhydro is the corrected value for mass gain obtained by dividing the molecular weight of a polymeric sugar by its monomer weight during its hydrolysis (0.90 for C6 sugars glucose, galactose and mannose and 0.88 for C5 sugars xylose and arabinose) and ODW is the oven dry weight of the sample in mg.
[0277] Determination of mother liquor composition
[0278] The lignin content of the ionic liquid / lignin solution (mother liquor) used for spinning is calculated based on the difference between the lignin content of the raw biomass and the lignin content in the ionosolv pulp (as determined by composition analysis), the pulp yield (based on oven dry weight) and the weight of the mother liquor obtained. The equations are shown below (Equations 5, 6 and 7):
[0279] W 木质素(生物质)=(AIL%+ASL%)·ODW 生物质 (5)
[0280] W 木质素(纸浆) =(AIL%+ASL%)·ODW 纸浆 (6)
[0281]
[0282] Where W 木质素(生物质) and W 木质素(纸浆) are the weight of lignin in virgin biomass and eucalyptus pulp, respectively; ODW 生物质 and ODW 纸浆 are the oven-dry weights of raw wood and pulp, respectively; lignin% (lq) is the lignin concentration in the mother liquor in wt% and W 母液 is the weight of the mother liquor.
[0283] Determine the water content using a coulometric Karl Fischer titrator. 1 H-NMR spectroscopy determines the ionic liquid and residual ethanol content. The signal of the methyl group on ethanol (δH (400MHz, DMSO-d6) / ppm: 1.05, t) and the signal of the methyl group on the butyl chain of [DMBA][HSO4] (δH (400MHz, DMSO-d6) / ppm: 0.90, t) are used to calculate the molar ratio of ionic liquid and EtOH, which is converted into a weight ratio by multiplying with the molecular weight of each molecule. The ionic liquid and EtOH content in the mother liquor can be calculated according to the following equations (8) and (9):
[0284]
[0285] Where IL% (1q), EtOH% (1q) and water% (1q) are the weight percentages of ionic liquid, EtOH and water in the mother liquor, respectively. IL,ETOH% It is based on 1 The weight ratio of ionic liquid to EtOH was calculated from the molar ratio obtained by H-NMR spectroscopy.
[0286] Preparation of spinning solution
[0287] The spinning solution can be prepared by adding the carbon nanomaterial to the mother solution produced in the previous step, optionally also adjusting the water content if necessary. Shearing can be applied to disperse the carbon nanomaterial to provide a spinning solution. The spinning solution can then be extruded into a coagulant as described herein to produce fibers.
[0288] Example 5: Aging Study
[0289] This embodiment studies the effect of the storage time length of lignin solution (lignin dissolved in [DMBA][HSO4] with a water content of 5%). Two experiments were conducted. One experiment was conducted when the lignin solution was prepared (0 day experiment), and the other experiment was conducted after 1 month (30 days).
[0290] method
[0291] 1. A solution containing lignin (12 wt %) dissolved in [DMBA][HSO4] (containing 5.02% H2O) was prepared using a THINKY mixer (ARM-310) at 2000 rpm for 1 hour.
[0292] 2. This solution was used to disperse single wall nanotubes (SWNT) in a pestle and mortar for 60 minutes. The spinning solution was transferred to a syringe and wet spun into a rotating coagulation bath containing H2O (200 ml) at an extrusion rate of 0.009 ml / min using a 27G needle.
[0293] 3. Allow the fiber to coagulate for 15 minutes, pick up with forceps and hang on a drying wire with a foil weight (15-20 mg) to keep the fiber straight and under tension.
[0294] 4. The remaining lignin solution in [DMBA][HSO4] was aged for one month (30 days) and then the SWNTs were dispersed using a pestle and mortar in the same manner.
[0295] 5. The stock solution with aged lignin solution (30 days) was transferred to a syringe and wet-spun in the same manner as above.
[0296] 6. The 30-day fiber was continuously spun and had higher fiber integrity than the 0-day fiber, and therefore the 30-day fiber was heat stabilized by heat treatment (from 25°C to 100°C at 1°C / min, then from 100°C to 250°C at 0.2°C / min, and kept at 250°C for 1 hour), and then carbonized to 1000°C at 1°C / min, and kept at 1000°C for 1 hour.
[0297] 7. Collect the fibers and prepare for tensile testing.
[0298] Optical Microscope
[0299] When the stock samples were examined by optical microscopy, there were no visual differences between the stock samples. The dispersion quality of the SWNTs for both was of good quality (well-dispersed CNTs), as assessed by the absence of large CNT aggregates (>20 μm). Since most of the stock solutions appeared homogeneous, they were considered suitable for wet spinning.
[0300] Rheology
[0301] The shear viscosity of the composite stock solutions was slightly different. It was found that the viscosity of the 0-day stock solution was higher than that of the 30-day stock solution ( Figure 6 ). Both stock solutions exhibit shear thinning behavior. The lower viscosity stock solution (30 days) may be associated with improved spinnability compared to the higher viscosity 0 day stock solution.
[0302] Fiber characterization
[0303] Short fibers (6-7 cm) can be obtained from the 0-day stock solution, and these fibers can be used for characterizations (Scanning Electron Microscopy (SEM) and TGA) where short fiber length is required. For the purpose of this study, the fibers needed to be at least 13-14 cm long for carbonization because a graphite bridge with a fixed length (10 cm) was used to mount the fibers.
[0304] The fibers prepared from the 30-day stock solution were more uniform and spun continuously. The fibers had higher integrity when lifted, so longer fibers (>40 cm) could be obtained. The cross-sectional area of the fibers also looked more rounded compared to the fibers obtained from the 0-day stock solution. These fibers were moved to the next stage of the process for heat stabilization and then carbonization.
[0305] Tensile test
[0306] The mechanical properties of the 30 day fibers were tested and found to range between 200 and 400 MPa (Table 1).
[0307] Table 1: Tensile test data of fibers carbonized for 30 days.
[0308]
[0309]
[0310] It should be understood that the above description is made by way of example and not to limit the scope of the appended claims, including any equivalents included within the scope of the claims. Various modifications are possible and will be apparent to those skilled in the art.
[0311] Likewise, features of the described embodiments may be combined with any appropriate aspects described above, and optional features of any one aspect may be combined with any other appropriate aspects.
Claims
1. A method for producing a fiber, the method comprising: Providing a spinning solution, the spinning solution comprising a solution solvent, lignin dissolved in the solution solvent, and a carbon nanomaterial, wherein the solution solvent comprises an ionic liquid and optionally water; and The spinning solution is extruded into a coagulant to obtain one or more fibers.
2. The method according to claim 1, wherein the water content of the stock solution solvent is 0-30wt%, 0-20wt%, 0-15wt%, 0-10wt% or 0-5wt%.
3. The method according to claim 1 or 2, wherein the stock solution solvent comprises at least 1 wt% water, at least 2 wt% water or at least 3 wt% water.
4. The method according to any one of the preceding claims, wherein the lignin is present in a loading of at least 10% relative to the mass of the spinning solution, excluding the mass of lignin and carbon nanomaterial.
5. The method according to claim 4, wherein the lignin is present in a loading amount of 10-50%, 10-40%, 10-30% relative to the mass of the spinning solution, excluding the mass of lignin and carbon nanomaterials.
6. The method according to any one of the preceding claims, wherein the carbon nanomaterial is present in a loading amount of at least 0.001%, at least 0.01% or at least 0.1% relative to the mass of the spinning solution, excluding the mass of lignin and carbon nanomaterial.
7. A method according to any one of the preceding claims, wherein the carbon nanomaterial is present in a loading amount of 0.001-10%, 0.001-8%, 0.01-8%, 0.1-5%, 0.1-1% or 0.3-0.7% relative to the mass of the spinning solution, excluding the mass of lignin and carbon nanomaterial.
8. The method according to any one of the preceding claims, wherein the weight ratio of lignin to carbon nanomaterial in the spinning solution is 5:1 to 10000:1, 5:1 to 5000:1, 10:1 to 1000:1 or 20:1 to 200:
1.
9. The method according to any one of the preceding claims, wherein the carbon nanomaterial is dispersed in the stock solution solvent.
10. The method according to any one of the preceding claims, wherein the carbon nanomaterial comprises carbon nanotubes, carbon nanoribbons, graphene nanoplates or combinations thereof.
11. The method of claim 10, wherein the carbon nanomaterial comprises carbon nanotubes, optionally wherein the carbon nanotubes are single-walled carbon nanotubes (SWCNTs).
12. The method according to any one of the preceding claims, wherein the ionic liquid comprises a cation and an anion selected from the group consisting of: C 1-20 Alkyl sulfate ion ([alkyl SO4]-), C 1-20 Alkyl sulfonate ions ([alkyl SO3]-), hydrogen sulfate ions ([HSO4] - ), bisulfite ion ([HSO3] - ), dihydrogen phosphate ion ([H2PO4] - ), hydrogen phosphate ion ([HPO4] 2- ), chloride ion (Cl - ), bromide ion (Br - ), trifluoromethanesulfonate ion ([OTf] - ), formate ion ([HCOO] - ) and acetate ions ([MeCO2] - ), optionally wherein the anion is selected from [HSO4] - and [HCOO] - .
13. A method according to any one of the preceding claims, wherein the ionic liquid comprises a cation and an anion, wherein the cation contains a nitrogen-containing heterocyclic moiety, or wherein the cation is a cation of formula I: Among them A 1 To A 4 Each independently selected from H, aliphatic, C 3-6 Carbon ring, C 6-10 Aryl, alkaryl and heteroaryl.
14. The method according to any one of the preceding claims, wherein the ionic liquid is an [alkylammonium][HSO4] or [alkylammonium][HCOO] ionic liquid.
15. The method according to any one of the preceding claims, wherein the ionic liquid is triethylammonium hydrogen sulfate [TEA][HSO4], N,N-dimethylbutylammonium hydrogen sulfate [DMBA][HSO4], diethylammonium hydrogen sulfate [DEA][HSO4], N,N-dimethylethylammonium hydrogen sulfate ([DMEA][HSO4]), diethanolammonium chloride [DEtOHA] Cl, 1-methylimidazolium hydrochloride [HMim] Cl, 1-ethyl-3-methylimidazolium chloride [EMim] Cl and 1-ethyl-3-methylimidazolium trifluoromethanesulfonate [EMim][OTf] , 1-butylimidazolium hydrogen sulfate ([HBim][HSO4]), methylbutylammonium hydrogen sulfate ([MBA][HSO4]), 1-methylimidazolium formate ([HMim][HCOO]), N,N-dimethylbutylammonium formate ([DMBA][HCOO]), N,N-dimethylethylammonium hydrogen sulfate ([DMEA][HSO4]), 1-butyl-3-methylimidazolium hydrogen sulfate [BMim][HSO4] or N-dimethylbutylammonium acetate ([DMBA][OAc]) or a mixture thereof, preferably wherein the ionic liquid is [DMBA][HSO4].
16. The method according to any one of the preceding claims, wherein the stock solution solvent further comprises ethanol, optionally wherein the ethanol is present at 1-20 wt%, preferably 5-15 wt%, relative to the total weight of the stock solution solvent.
17. The method according to any one of the preceding claims, wherein the coagulant comprises water.
18. The method according to any one of the preceding claims, wherein the coagulant: (a) comprising water and an ionic liquid, wherein the ionic liquid is present in an amount of no more than 60 wt%, no more than 30 wt% or no more than 15 wt%, preferably 1-60 wt%, 1-30 wt% or 1-15 wt%, more preferably 5-10 wt% relative to the total mass of the coagulant; or (b) contains water and sodium sulfate.
19. The method according to any one of the preceding claims, wherein the spinning solution is prepared by a method comprising preparing a lignin solution and combining the lignin solution with the carbon nanomaterial; wherein the lignin solution is prepared by: a) contacting a lignocellulosic biomass comprising lignin and cellulose with a composition comprising an ionic liquid and water (preferably 5-40 wt% water) to dissolve the lignin and produce a cellulose pulp; b) separating the cellulose pulp to obtain a mother liquor comprising the ionic liquid, water and lignin; and c) optionally adjusting the amount of ionic liquid and / or water in the mother liquor to obtain the lignin solution.
20. The method according to claim 19, wherein the lignocellulosic biomass is contacted with the composition at 100-180°C, preferably 120-170°C.
21. The method of any one of the preceding claims, further comprising drying the one or more fibers by: (a) under mechanical tension; and / or (b) by heating the one or more fibers, optionally at 150-300° C. in air.
22. The method according to any one of the preceding claims, further comprising carbonizing the one or more fibers to obtain carbon fibers, optionally wherein the carbonizing comprises heating the one or more fibers to 800-3000°C, preferably 1200-1800°C under an inert atmosphere.
23. A fiber obtainable by a process according to the preceding claim.
24. A spinning solution comprising a solution solvent, lignin and a carbon nanomaterial, wherein the solution solvent comprises an ionic liquid and optionally water.
25. A dispersion comprising carbon nanotubes and [DMBA][HSO4].
Citation Information
Patent Citations
treatment
WO2012080702A2
treatment
WO2014140643A1
Process for the extraction of metal pollutants from treated cellulosic biomass
WO2017085516A1